Evaluasi Kemampuan Adaptasi Dan Efisiensi Pakan Ikan Kepala Timah (Aplocheilus Panchax) Pada Sistem Pemeliharaan Terkontrol - Ikram, Muhammad Fatih; Arroyyan, Muhammad Syafa; Ramadani, Ayu; Dhila, Titania Aisyah; Kurniawan, Ardiansyah (Jurnal Perikanan dan Kelautan, 2025)
This study aims to assess the conservation efforts of the Spotted Blue-eye (Aplocheilus panchax) through adaptation and maintenance in controlled environments. Thirty wild-caught individuals were reared for two months and fed with dried shrimp and commercial pellets. The results showed excellent adaptability, indicated by a 100% survival rate under optimal water quality conditions (pH 7.56; DO 7.4 mg/L; temperature 26.2°C). Growth performance was satisfactory, with a specific growth rate (SGR) of 1.96%, although the feed conversion ratio (FCR) remained relatively high at 6.25. It is concluded that A. panchax can adapt and grow well under controlled rearing conditions, although improvements in feeding management are needed to enhance culture efficiency. The development of A. panchax culture not only has the potential to enhance the diversification of aquaculture commodities but also contributes to the conservation of local species by reducing fishing pressure on wild populations.